KONEKTIVITAS ELEMEN EKOSISTEM KEWIRAUSAHAAN PERTANIAN DI KABUPATEN BOGOR - Syhabuddin Al Tapsi; Lukman Mohammad Baga; Feryanto (Jurusan Manajemen FEB UHO, 2024)
Although the agricultural sector supported the economic structure of Bogor Regency, its contribution still needs to be higher compared to other sectors. This condition was caused individual capabilities as an agricultural entrepreneur and the agricultural entrepreneurship ecosystem in Bogor Regency are not conducive. Thus, this study aimed to analyze the interaction of the elements of the agricultural entrepreneurship ecosystem in Bogor Regency. This research used a quantitative approach with descriptive statistical analysis to analyze the relationship between elements of the urban entrepreneurial ecosystem. The locations were selected by purposively selecting areas with the highest agricultural contribution. The analysis used correlation data obtained from a survey of 110 agricultural entrepreneurs with a questionnaire on a Likert scale of 1 – 5. The analysis showed that the correlation value between ecosystem elements tended to be low, indicating that the level of dependence between elements in shaping the agricultural entrepreneurship ecosystem in Bogor Regency was still weak. The analysis also showed that, demand and leadership were central in the interdependent network based on the number and high strength of pathways.